2018
DOI: 10.1053/j.jfas.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Extensor Hallucis Longus Variants Featuring a Novel Extensor Primi Internodii Hallucis Muscle Merging With Extensor Hallucis Brevis

Abstract: The extensor hallucis longus (EHL) muscle/tendon complex has been used in a variety of tendon transfer and tenodesis surgeries to correct iatrogenic hallux varus deformity, equinovarus foot deformity, clawed hallux associated with a cavus foot, and dynamic hyperextension of the hallux and, even, to prevent pedal imbalance after transmetatarsal amputation. Although it is usually considered a unipennate muscle inserting into the dorsum of the base of the distal phalanx of the hallux, a vast majority of EHL muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The EHL is characterized by morphological variability with regard to the number of its additional bands and their insertion [1, 3–7]. Most previous research has focused on its possible morphological variations, particularly those regarding the additional bands.…”
Section: Introductionmentioning
confidence: 99%
“…The EHL is characterized by morphological variability with regard to the number of its additional bands and their insertion [1, 3–7]. Most previous research has focused on its possible morphological variations, particularly those regarding the additional bands.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are documented to show multiple muscular variations, unilateral, or bilateral, in extensors of foot in cadavers. [6][7][8][9][10][11][12][13][14][15] In the present study, bifurcation of EHL tendon was having medial and lateral slips. Medial slip was the main extensor tendon of great toe, whereas lateral slip was extensor tendon of 2 nd toe.…”
Section: Discussionmentioning
confidence: 88%
“…4 These variations manifest as painful foot on some occasions due to impingement of the surrounding structures. 5 Although various studies have already been conducted representing the variations in extensor tendons of foot, [6][7][8][9][10][11][12][13][14][15] the variations found in our study are rare and have not been previously reported in the literature. Description of tendons in foot is prerequisite for the surgeons to decide for suitable graft in various reconstructive surgeries and for the analysis of injuries in tendons.…”
Section: Introductionmentioning
confidence: 79%
“…Ancillary muscles are the sartorius muscle, the gracilis, the popliteus muscle, the gastrocnemius and the soleus muscle. In addition, for the left foot to move right and in front of the above walking muscles, the adductor muscles (the adductor magnus, the adductor minimus, the adductor longus and the gracilis) also participate (Zdilla, Paulet, Lear, Addie, & Lambert, 2018;Olewnik, Podgorski, M., Polguj, M. Ruzik, K., & Topol, 2019;Bordoni & Varacallo, 2020).…”
Section: Basic Strokes C1 Forehand Drivementioning
confidence: 99%